Packing Death in Australian Literature Ecocides and Eco-Sides. - Ralph, Iris. (Milton : Taylor & Francis Group, 2020)
Packing Death in Australian Literature: Ecocides and Eco-Sidesaddresses Australian Literature from ecocritical, animal studies, plantstudies, indigenous studies, and posthumanist critical perspectives. Thebook's main purpose is twofold: to bring more sustained attention to environmental,vegetal, and animal rights issues, past and present, and todo that from within the discipline of literary studies. Literary studies inAustralia continue to reflect disinterest or not enough interest in criticalengagements with the subjects of Australia's oldest extant environmentsand other beings beside humans. Packing Death in Australian Literature:Ecocides and Eco-Sides foregrounds the vegetal and nonhumananimal populations and contours of Australian Literature. Critical studiesrelied on in Packing Death in Australian Literature: Ecocides andEco-Sides include books by CA. Cranston and Robert Zeller, Simon C.Estok, Bill Gammage, Timothy Morton, Bruce Pascoe, Val Plumwood,Kate Rigby, John Ryan, Wendy Wheeler, and Cary Wolfe. The selectedliterary texts include work by Merlinda Bobis, Eric Yoshiaki Dando,Nugi Garimara, Francesca Rendle-Short, Patrick White, and Evie Wyld.
Translation Studies: Tips for Translating the Nonhuman Other -- Wish -- Tracks -- Listening -- 6 Conclusion -- Ecophobia -- Ecocriticism and Object-Oriented-Ontology -- Riders in the Chariot -- Final Remarks: "Openness from Closure" -- Works Cited -- Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Ecocriticism in literature; Australian literature -- History and criticism; Environmentalism in literature; LITERARY CRITICISM / General